Cancer incidence among women and girls environmentally and occupationally exposed to blue asbestos at Wittenoom, Western Australia - Reid, Alison; Heyworth, J.; De Klerk, N.; Musk, B. (John Wiley & Sons, Inc., 2008)
The impact of crocidolite exposure on the health of former Wittenoom miners and millers (largely male) has been well documented. Less is known about the health outcomes of the 2,968 women and girls who lived (N = 2,552) and worked (N = 416) in the blue asbestos milling and mining town of Wittenoom between 1943 and 1992. Quantitative exposure measurements were derived from dust studies undertaken over the lifetime of the mine and mill and the township. Incident cancers were obtained from the Western Australian (WA) Cancer Registry and the National Cancer Clearing House. Standardized incidence ratios (SIRS) compared Wittenoom females with the WA female population. Exposure-response relationships were examined using a matched case-control study design. There were (47) mesothelioma and (55) lung cancer cases among the 437 cancers in the Wittenoom females over the period 1960-2005. When compared to the WA female population, Wittenoom women and girls had higher rates of mesothelioma and possibly lung cancer. Mesothelioma incidence rates are increasing with the incidence rate of 193 per 100,000 in the period 2000-2005 being more than double that for the period 1995-1999 at 84 per 100,000. A significant exposure-response relationship was present for mesothelioma, but not for lung cancer. Forty years after the asbestos mine and mill at Wittenoom were closed, there is a high toll from cancer among the former female residents of the town and company workers. © 2007 Wiley-Liss, Inc.